Flow cytometric method for cell viability evaluation of Gordonia alkanivorans strain 1B in fossil fuels biodesulfurization processes - Teixeira, A. V. (2013)
The most commonly method used for sulfur removal from fossil fuels is hydrodesulfurization, a physico-chemical process at very high temperatures and pressures. An alternative to this process is biodedesulfurization (BDS), a microbiological process that works at atmospheric pressure and temperature making it easier to work with and less expensive. It also as the advantage of easily desulfurizing recalcitrant sulfur compounds which are hard to remove by hydrodesulfurization [1]. Several bacteria species, such as Gordonia alkanivorans strain1B [2], are able to desulfurize dibenzothiophene, a model compound used commonly in BDS studies, to 2-hydroxybiphenyl (2-HBP) via the 4S pathway without destroying the carbon structure [3], therefore maintaining the fuel potential energy. BDS limitations are related with process parameters and with the cost of maintaining bacterial cultures so to enhance the BDS process, it is necessary to monitor how changes in the experimental system affect the microbial cells viability and consequently the process efficiency. An alternative method to conventional microbial techniques to determine cell viability is flow cytometry. This method provides a fast and accurate quantitative method for measurement of thousands of individual cells, based on scattered light and fluorescence emitted by specific dyes. The goal of this study was to develop a rapid method for viability assessment of G. alkanivorans cells using flow cytometry for further application to monitor and optimize BDS processes.